2020
DOI: 10.1111/jcmm.15154
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass grafting is associated with immunoparalysis of monocytes and dendritic cells

Abstract: Coronary artery bypass grafting (CABG) triggers a systemic inflammatory response that may contribute to adverse outcomes. Dendritic cells (DC) and monocytes are immunoregulatory cells potentially affected by CABG, contributing to an altered immune state. This study investigated changes in DC and monocyte responses in CABG patients at 5 time-points: admission, peri-operative, ICU, day 3 and day 5. Whole blood from 49 CABG patients was used in an ex vivo whole blood culture model to prospectively assess DC and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…definition of innate immunoparalysis mediated by ECMO ( 92 ). The observed changes are also in line with profiles associated with sepsis, and nosocomial infections in post-CPB cardiac surgery and VAD implanted patients ( 40 , 41 , 49 ).…”
Section: What Are the Implications Of Leukocyte Modulation In Ecmo Pasupporting
confidence: 79%
See 2 more Smart Citations
“…definition of innate immunoparalysis mediated by ECMO ( 92 ). The observed changes are also in line with profiles associated with sepsis, and nosocomial infections in post-CPB cardiac surgery and VAD implanted patients ( 40 , 41 , 49 ).…”
Section: What Are the Implications Of Leukocyte Modulation In Ecmo Pasupporting
confidence: 79%
“…Existing research reported alteration of leukocyte numbers, phenotype, and functions with non-specific activation when ECMO is used ( Tables 1 and 2 ). A similar response has been observed in other extracorporeal circulatory modalities preceding ECMO, such as cardiopulmonary bypass (CPB), renal replacement therapy, and ventricular assist devices (VAD) ( 40 49 ). The sequelae linked to inappropriate leukocyte modulation can be detrimental.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Dendritic cells are important regulatory immune cells at the interface of the innate and adaptive immune system. The ability of dendritic cells to produce cytokines and express activation and co-stimulatory markers confirms immune competence 24 . Dendritic cell immune profile was assessed following exposure of the patient’s preoperative blood to ABT or their own ICS.…”
Section: Resultsmentioning
confidence: 85%
“…Existing research reported alteration of leukocyte numbers, phenotype, and functions with non-specific activation when ECMO is used (Tables 1 and 2). A similar response has been observed in other extracorporeal circulatory modalities preceding ECMO, such as cardiopulmonary bypass (CPB), renal replacement therapy, and ventricular assist devices (VAD) (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The sequelae linked to inappropriate leukocyte modulation can be detrimental.…”
Section: Introductionmentioning
confidence: 55%